Delivering on the Climate Emergency Towards a Net Zero Carbon Built Environment - Prasad, Deo.; Kuru, Aysu.; Oldfield, Philip; Ding, Lan.; Dave, Malay; Noller, Caroline; He, Baojie (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
"This book provides much needed insights into the scale and nature of the challenges we all face in reducing the impact of built environments on our shared climate. It plots safer pathways forward for reducing operational and embodied energy in construction and refurbishment. It should be mandatory reading for all designers, planners and developers in Australia." -Sue Roaf, Emeritus Professor, Heriot Watt University, UK "This book shows how, using science-based approaches, we can deliver on net zero carbon new buildings by 2030 and for existing ones we can do this by 2040. We need a whole of life and whole building approach. This book can be used in many countries and even localised with local data and benchmarks. A great publication." -Professor Wu Jiang, Chairman, Asia Architecture Association This book focuses on the transition towards net-zero carbon built environments to deliver on the climate emergency. It provides an evidence-based roadmap and proposes guidelines to achieving targets covering emerging technologies, materials, innovative design, regulations and policies. Scientia Professor Deo Prasad AO is the CEO of the NSW Decarbonisation Innovation Hub based at UNSW Sydney Australia. Dr Aysu Kuru is a lecturer at School of Architecture, Design and Planning, University of Sydney. Dr Philip Oldfield is Associate Professor and Head of School at UNSW Built Environment, Australia. Dr Lan Ding is Associate Professor and Convenor of High-Performance Architecture at UNSW Built Environment, Australia. Dr Malay Dave is Strategic Sustainability Advisor at Steensen Varming, Australia. Dr Caroline Noller is Chair of TG2 MECLA and a member of Australian Architects Declare's Technical Work Group. Dr Baojie He is Research Professor at School of Architecture and Urban Planning, Chongqing University, China.
1 The Climate Emergency and the Built Environment -- 2 Operational Carbon in the Built Environment: Measurements, Benchmarks and Pathways to Net Zero -- 3 Embodied Carbon in the Built Environment: Measurements, Benchmarks and Pathways to Net Zero -- 4 Delivering a Net Zero Carbon Built Environment: Synthesis, Measurability, Targets and Reporting -- 5 Case Studies: Exemplars to Learn From -- 6 Policy Pathways to a Net Zero Carbon Built Environment -- 7 Conclusions and Recommendations: Envisioning a Net Zero Carbon Future in the Built Environment.
Keywords: Human geography; Sustainable architecture; Sociology, Urban; Human Geography; Sustainable Architecture/Green Buildings; Urban Sociology